The Influence of Price Perceptions, Promotions and Service Quality on Repurchase Decisions - Irawan Rumatiga (Journal of Management Research and Studies, 2023)
This research aims to determine the influence of price perceptions, promotions and service quality on repeat purchase decisions. The sampling technique used in this research is nonprobability sampling with a total of 100 respondents. Research location, namely Shankara Rent, Malang City.  The data collection techniques are documentation, questionnaires and observation, the information used is secondary and primary. And the data is processed through software IBM SPSS Statistics 25. The results of this research show that, 1). Price Perception can partially increase Consumer Repurchase Decisions. 2). Promotion can partially increase consumer repurchase decisions. 3). Service Quality is partially able to increase Consumer Repurchase Decisions. 4). Price Perception, Promotion, and Service Quality can simultaneously increase Consumer Repurchase Decisions. 5). Service Quality is the dominant factor that can increase Consumer Repurchase Decisions.